2016
DOI: 10.1002/leap.1050
|View full text |Cite
|
Sign up to set email alerts
|

Colleagues helping each other to publish in medical sciences: Iranian field specialists' convenience editing strategies

Abstract: This article reports a study into 60 research articles (RAs) authored by Iranian medical researchers and published in high-quality international English journals. It investigated how academic professionals in medical sciences implement peer convenience editing (CE) to improve articles and make them suitable for publication. The research identified nine editing interventions that were categorized as micro-or macro-editing strategies.The findings indicated that the most frequently used strategies are microstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…This reluctance to offer discursive assistance to colleagues has also been noted elsewhere so, for instance, the Iranian healthcare academics in Gholami and Zeinolabedini's (2017) study felt "overtaxed" when asked to edit papers by fellow medical professionals. When they did provide help, moreover, their busy schedule meant they provided very limited textual interventions as we noted above for DS2's paper (Zeinolabedini and Gholami 2016). On the other hand, Lillis and Curry (2010) report how an Anglophone-centre researcher substantially shaped two European academics' manuscript, but we suspect this is not a representative case.…”
Section: 此句写清楚,随着病程的进展,血清胸腺素的含量逐渐增加。(Translationmentioning
confidence: 93%
See 1 more Smart Citation
“…This reluctance to offer discursive assistance to colleagues has also been noted elsewhere so, for instance, the Iranian healthcare academics in Gholami and Zeinolabedini's (2017) study felt "overtaxed" when asked to edit papers by fellow medical professionals. When they did provide help, moreover, their busy schedule meant they provided very limited textual interventions as we noted above for DS2's paper (Zeinolabedini and Gholami 2016). On the other hand, Lillis and Curry (2010) report how an Anglophone-centre researcher substantially shaped two European academics' manuscript, but we suspect this is not a representative case.…”
Section: 此句写清楚,随着病程的进展,血清胸腺素的含量逐渐增加。(Translationmentioning
confidence: 93%
“…However, Lillis and Curry (2010), investigating non-Anglophone European academics in education and psychology, conclude that colleagues are the most valuable publishing resource for EAL scholars, a finding echoed by Li (2014b) studying a group of surgeons at a Chinese hospital. Research on Iranian medical scholars, on the other hand, found that colleagues lacked the confidence and literacy skills to rectify their fellow researchers' papers (Gholami and Zeinolabedini 2017;Zeinolabedini and Gholami 2016).…”
Section: Collegial Support For Eal Academicsmentioning
confidence: 99%
“…To improve the language of their manuscripts, many EAL scholars have turned to fee‐paying ‘literacy brokers’ (Bowker & Ciro, 2019)—a term first coined by Lillis and Curry (2010) to refer to such helpers as translators, proofreaders or editors in the process of publication—or ‘text mediators’ (Luo & Hyland, 2016, 2019), which is similar to ‘literacy brokers’ in denotation but can be either fee‐paying or free. Some have sought convenience editing services from supervisors and colleagues (Luo & Hyland, 2021; Maniati & Jalilifar, 2018; Zeinolabedini & Gholami, 2016) or cooperated extensively with supervisors, colleagues or even students able to improve the language as coauthors (Mu, 2020). Imitation, especially language‐reuse or the use of formulaic sequences has also been a common technique used by EAL scholars in the process of writing or revising manuscripts (Abbas et al, 2020; Flowerdew & Li, 2007; Li, 2005; Mu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the Chinese introductions emphasized the use of endophorics, attitude markers, and engagement markers. Zeinolabedini and Gholami (2016) analyzed 60 research articles which were written by Iranian medical researchers in order to examine the role of peer convenience editing in the improvement of medical professionals' articles. This study enumerated nine editing interventions classified into two strategy groups, including micro and macro editing strategies.…”
Section: Introductionmentioning
confidence: 99%